Combination of Bempegaldesleukin and Anti-CTLA-4 Prevents Metastatic Dissemination After Primary Resection or Radiotherapy in a Preclinical Model of Non-Small Cell Lung Cancer - Bates, Amber M.; Brown, Ryan J.; Pieper, Alexander A.; Zangl, Luke M.; Arthur, Ian; Carlson, Peter M.; Le, Trang; Sosa, Gustavo A.; Clark, Paul A.; Sriramaneni, Raghava N.; Kim, KyungMann; Patel, Ravi B.; et al. (Frontiers in Oncology, 2021)
Surgical resection or hypo-fractionated radiation therapy (RT) in early-stage non-small cell lung cancer (NSCLC) achieves local tumor control, but metastatic relapse remains a challenge. We hypothesized that immunotherapy with anti-CTLA-4 and bempegaldesleukin (BEMPEG; NKTR-214), a CD122-preferential IL2 pathway agonist, after primary tumor RT or resection would reduce metastases in a syngeneic murine NSCLC model. Mice bearing Lewis Lung Carcinoma (LLC) tumors were treated with combinations of BEMPEG, anti-CTLA-4, and primary tumor treatment (surgical resection or RT). Primary tumor size, mouse survival, and metastatic disease at the time of death were assessed. Flow cytometry, qRT-PCR, and cytokine analyses were performed on tumor specimens. All mice treated with RT or surgical resection of primary tumor alone succumbed to metastatic disease, and all mice treated with BEMPEG and/or anti-CTLA-4 succumbed to primary tumor local progression. The combination of primary tumor RT or resection and BEMPEG and anti-CTLA-4 reduced spontaneous metastasis and improved survival without any noted toxicity. Flow cytometric immunoprofiling of primary tumors revealed increased CD8 T and NK cells and decreased T-regulatory cells with the combination of BEMPEG, anti-CTLA-4, and RT compared to RT alone. Increased expression of genes associated with tumor cell immune susceptibility, immune cell recruitment, and cytotoxic T lymphocyte activation were observed in tumors of mice treated with BEMPEG, anti-CTLA-4, and RT. The combination of BEMPEG and anti-CTLA-4 with primary tumor RT or resection enabled effective control of local and metastatic disease in a preclinical murine NSCLC model. This therapeutic combination has important translational potential for patients with early-stage NSCLC and other cancers.